Filaggrin loss‐of‐function mutations and incident cancer: a population‐based study. (1st December 2014) - Skaaby, T.; Husemoen, L.L.N.; Thyssen, J.P.; Meldgaard, M.; Thuesen, B.H.; Pisinger, C.; Jørgensen, T.; Carlsen, K.; Johansen, J.D.; Menné, T.; Szecsi, P.B.; Stender, S.; et al.
Summary: Background: Loss‐of‐function mutations in the filaggrin gene ( FLG ) could have opposing effects on cancer risk, as mutations are associated with both 10% higher serum vitamin D levels, which may protect against cancer, and with impaired skin barrier function, which may lead to higher cancer susceptibility. Objectives: To investigate the association of the FLG genotype and cancer types in four population‐based cohorts. Methods: A total of 13 376 individuals were genotyped for FLG mutations. Information on cancer was obtained from the Danish Cancer Registry. Persons with a history of cancer at baseline were excluded from prospective analyses. Results: There were 1339 incident cancers (median follow‐up 11·4 years). The hazard ratios (HRs) and 95% confidence intervals (CIs) for FLG mutation carriers vs. wild types were: for any cancer (HR 0·95, 95% CI 0·78–1·16), any cancer excluding nonmelanoma skin cancer (NMSC) (HR 1·05, 95% CI 0·84–1·31), head and neck cancer (HR 1·72, 95% CI 0·71–4·15), colorectal cancer (HR 0·82, 95% CI 0·44–1·52), bronchus and lung cancer (HR 1·34, 95% CI 0·77–2·33), breast cancer (HR 0·58, 95% CI 0·30–1·14), uterine cancer (HR 0·42, 95% CI 0·06–3·10), prostate cancer (HR 1·09, 95% CI 0·61–1·94), urinary cancer (HR 1·30, 95% CI 0·51–3·29), malignant melanoma (HR 1·03, 95% CI 0·41–2·58) and NMSC (HR 0·70, 95% CI 0·47–1·05). Among participants aged over 60 years at baseline, we found statistically significant lower risks of all cancers and NMSC among FLG mutation carriers. Conclusions: The only significant associations between FLG loss‐of‐function mutations and cancer were in subgroup analyses.